Peran Inovasi Untuk Meningkatkan Literasi Masyarakat Melalui Pengembangan Perpustakaan Masjid Al Jarwal Ar Rahman Purwakarta - Pri Agung Danarahmanto; Raden Willa Permatasari; Elpy Siti Nurhalimah Sariwanodja; Sigit Djalu Purwoko (Jurnal Multidisiplin Madani, 2022)
Science is a constituent part of human civilization and culture. Knowledge can be obtained from various things, one of which is from libraries. The existence of the library can not be separated from the civilization and culture of mankind. This study aims to conduct a study on the role of innovation to improve public literacy through library development. This study uses a qualitative approach by collecting data in the form of observations and interviews. The results of the innovation research are useful in the development of the AJAR Library which is a new library so that it is useful for improving literacy and providing continuous education for the community. The existence of the AJAR Library aims to arouse public interest and desire to continue reading and learning in order to realize sustainable education that has an impact on people's lives.